2005
DOI: 10.1002/cbic.200500175
|View full text |Cite
|
Sign up to set email alerts
|

The Folding and Unfolding Kinetics of the i‐Motif Structure Formed by the C‐Rich Strand of Human Telomere DNA

Abstract: Return to the fold. Nucleic acids with four tandem cytidine‐rich repeats can fold into a structure called the i‐motif at acidic pH. The folding‐ and unfolding‐rate constants of such a sequence in vertebrate telomere DNA were measured. Protons were found to promote i‐motif formation by increasing the folding and decreasing the unfolding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 38 publications
(51 reference statements)
3
32
0
Order By: Relevance
“…The half transition of this device at pH 6.2 was in close agreement with the reported transition of i-motif structure in bulk phase at pH 6.3 (see Supplementary Data, Figure S5) (41,46). The melting profile of the device at pH 4.5 was also found to be well consistent to the i-motif structure in bulk solution at pH 4.5 (see Supplementary Data, Figure S5).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The half transition of this device at pH 6.2 was in close agreement with the reported transition of i-motif structure in bulk phase at pH 6.3 (see Supplementary Data, Figure S5) (41,46). The melting profile of the device at pH 4.5 was also found to be well consistent to the i-motif structure in bulk solution at pH 4.5 (see Supplementary Data, Figure S5).…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure 4, typical relaxation time constants of the device opening and closing were measured to be ∼300 and ∼330 s respectively, which are much slower than folding and unfolding of i-motif structure in solution phase (14,41). In this study, alternating electric field was used to modulate molecular cooperative motion during the device switching, which provides a scalable means to accelerate the device response (12,42–45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same strategy, we investigate in the present work the formation pathway of i-motif tetramers formed by four identical TC n strands. The kinetics studies on i-motif previously reported concern mainly monomolecular (9) and dimeric (10) structures. Using UV absorption spectrophotometry (11), FRET (12) and NMR (10), it was shown that strand association and i-motif dissociation are relatively slow and that the i-motif stability is optimal around the cytidine pK.…”
Section: Introductionmentioning
confidence: 99%
“…35,[49][50][51][52][53] The latter deficiency may be partially due to the slow kinetics of complex formation, a feature which can compromise many indirect approaches used in thermodynamic analyses. 42,51,54,55 To address this deficiency, we have used a combination of spectroscopic and calorimetric techniques to characterize the energetics of i-DNA tetraplex formation. We previously used DSC to detect and characterize coupled conformational transitions in i-DNA and poly rA, a coupling that resulted in communication between noncontacting nucleic acid species.…”
mentioning
confidence: 99%